Evaluation of the crossings between local and drought-tolerant rice varieties using simple sequence repeat (SSR) molecular marker - Aditya Wahyudhi; Lintang Restu Pratiwi; Panjisakti Basunanda (Faculty of Agriculture, Universitas Gadjah Mada jointly with PISPI, 2021)
Two cultivars of local rice, namely Mentik Wangi and Mentik Susu, have been grown around west to south flank of Merapi volcano. They are highly valued for their good taste and cooking characteristics. An attempt to introduce drought-tolerant rice varieties has been conducted by crossing them with two sources, namely Kasalath and Bluebonnet. Molecular-assisted selection using a set of SSR markers was applied to check the F1 and F2 generation trueness and segregation. This research was conducted in the facilities of Department of Agronomy, Faculty of Agriculture, Universitas Gadjah Mada, Yogyakarta. The research was a field experiment arranged in a completely randomized design, consisting of Mentik Wangi, Mentik Susu, Bluebonnet, and Kasalath, as well as their crossings’ F1 and F2 plants as treatments. The SSR markers used are RM72, RM228, RM518, and RM20(A). Polymorphism test of the parents showed that polymorphism exists between local and donor parents, thus these markers were considered eligible for the F1 and F2 tests. The heterozygous individuals of F1 were 75% for Bluebonnet × Mentik Wangi, 44.4% for Bluebonnet × Mentik Susu, and 46.7% for Mentik Wangi × Bluebonnet; all were consistent in every primer used. We could not confirm that the F2 populations showed segregation pattern that followed Mendelian segregation in some crosses due to too small size of the sample. Heterozygous individuals in F2 showed the differences pattern for each marker, indicating that the location of the SSR markers were far from each other in the genome.